Impact of the COVID-19 Pandemic on Epidemiological Trends in Pediatric Cervical Abscess-Forming Infections - Shuhei Takahashi; Ai Kishino; Kentaro Miyai; Shigeru Takishima; Tae Omori; Hidehiro Furuno; Ryosei Iemura; Makoto Ono; Keisuke Ogasawara; Akito Sutani; Masayuki Nagasawa (Microorganisms)
Abscess-forming cervical bacterial infections are rare and serious infections. Methods: We retrospectively examined the trends in abscess-forming cervical bacterial infections in children who required inpatient treatment in three periods before (January 2016 to June 2020), during (July 2020 to December 2022) and after the COVID-19 pandemic (January 2023 to June 2024). Results: The study included 96 patients with superficial cervical abscesses and 111 patients with deep cervical abscesses (34 with retropharyngeal abscesses, 51 with peritonsillar abscesses, and 26 with deep neck abscesses). Both decreased during the COVID-19 pandemic and increased significantly after the COVID-19 pandemic compared to before the COVID-19 pandemic (0.94 ± 0.92 vs. 0.50 ± 0.72 vs. 1.67 ± 1.11/month, 0.93 ± 0.96 vs. 0.60 ± 0.84 vs. 2.39 ± 1.70/month), which was related with the trends of respiratory viral infections. Bacteria were identified in 79 of the 97 cases in which punctures were performed; however, there were no significant differences between the three periods. No significant changes were found in the pharyngeal streptococcal antigen positivity rate, rate of oral antibiotic use before hospitalization, length of hospital stay, or duration of antibiotic administration before and after the COVID-19 pandemic. Conclusions: The COVID-19 pandemic has affected the epidemiology of cervical abscess-forming bacterial infections in children. Although the reemergence of respiratory viral infections after the COVID-19 pandemic may be a factor, the cause of the doubling in the number of neck abscesses after the COVID-19 pandemic remains unclear and requires further investigation.